N6 -Methyladenosine Negatively Regulates Human Respiratory Syncytial Virus Replication - Figueroa, Fabian; Vega-Gibson, Alonso; Catrileo, Joseline; Gaete-Argel, Aracelly; Riquelme-Barrios, Sebastian; Alonso-Palomares, Luis Antonio; Tapia, Lorena I.; Valiente-Echeverría, Fernando; Soto-Rifo, Ricardo; Acevedo, Monica L. (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) is the most abundant internal modification described in eukaryotic mRNA and several viral RNA including human respiratory syncytial virus (HRSV). Here, we evaluated the impact of m6A writers, erasers and readers on HRSV genomic RNA accumulation and inclusion bodies assembly during viral replication. We observed that the METTL3/METTL14 m6A writer complex plays a negative role in HRSV protein synthesis and viral titers, while m6A erasers FTO and ALKBH5 had the opposite effect. We also observed that m6A readers YTHDF1-3 bind to the viral genomic RNA inducing a decrease in its intracellular levels and thus, inhibiting viral replication. Finally, we observed that overexpression of YTHDFs proteins caused a decrease in the size of inclusion bodies (IBs), accompanied by an increase in their number. METTL3 knockdown cells showed an opposite effect indicating that the dynamics of IBs assembly and coalescence are strongly affected by m6A readers in a mechanism dependent on m6A writers. Taken together, our results demonstrated that the m6A modification negatively affects HRSV replication, possibly through a mechanism involving the assembly of inclusion bodies, the main factories of viral genomic RNA synthesis.